ANALISIS PENGENDALIAN PENGADAAN OBAT-OBATAN PADA UPT FARMASI DAN ALKES KOTA YOGYAKARTA - , ARUM SOJA LUKITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Inventory is a problem that often occurs in a company, including those engaged in the field of pharmacy. The need for drugs, reagents, vaccines and medical equipment not deterministic so that inventory management is necessary in order to meet consumer demand and to manage problems that arise with the supply. UPT Farmasi dan Alkes Kota Yogyakarta is the distribution center of drugs, reagents, vaccines and medical devices and medical consumables, all health centers to existing mains in the city of Yogyakarta. UPT Farmasi has difficulties in determining lot size of orders in accordance with the volume of slots for each drug in the warehouse as well as determine when to do the booking. Under these constraints, research conducted to provide an alternative method of controlling the drug supply can resolve the issue. The method used to manage the procurement is using ABC-VEN analysis and min-max to determine the number of orders to re-order point as the reference time of booking. The analysis showed that there are 47 drugs including group A, group B included 52 drugs and 138 drugs including group C. In group A, there are 38 types of drugs including vital and 8 types of drugs including essential. The proposed methods generates turnover ratio (TOR) of 2.2, while the initial method TOR has a value of 1.7. It also produces lower inventory value than the initial method with the difference of Rp 163 407 957. ROP of the proposed method can also save the cost of emergency procurement as much as Rp 890,000.00. Based on these results, it can be concluded that the proposed method can increase the value of TOR and lower inventory value thus obtained an efficiency of 20.5%. That means the efficiency of inventory turnover on the proposed method is higher than the initial method.